Risks to responders safety and mitigation strategies during rescue work in natural disasters: a scoping review - Alzahrani, Yahya (Division of Emergency Medicine, 2022)
Introduction: Emergency medical services (EMS) who attend to natural disasters are at a high risk of experiencing numerous psychological and physical conditions that adversely affect their health and safety as well as their ability to serve their purpose. This study aimed to identify factors that affect EMS responders' health and safety in natural disasters and provide information to mitigate harm in future natural disasters. Methods: A scoping review was conducted to identify literature published between 2000 and 2020 relating to EMS responder safety in natural disasters according to a predetermined search strategy. Titles and abstracts were first screened, whereafter full texts were reviewed and extracted. Results: In total, 49 articles were identified and 22 articles were ultimately included. The findings from the research identified numerous factors and outcomes that affect the health and safety of responders attending to disasters. These could be categorised into mental and psychological issues (PTSD, suicidal ideation, depression) and physical issues (environmental, infectious, and traumatic conditions). Conclusion: Numerous health and safety hazards befall responders attending to natural disasters and the variability of their incidence commands case-specific prevention and mitigation strategies. There is poor monitoring of factors affecting the health and safety of responders as well as their consequences, making current mitigation and prevention strategies ineffective. Enhanced surveillance and reporting systems should be developed and implemented to inform and improve mitigation strategies.